2020
DOI: 10.3174/ajnr.a6625
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraoperative Sonography and Histopathologic Evaluation of Tumor Thickness and Depth of Invasion in Oral Tongue Cancer: A Pilot Study

Abstract: BACKGROUND AND PURPOSE: For primary squamous cell carcinoma of the oral tongue, accurate assessment of tumor thickness and depth of invasion is critical for staging and operative management. Currently, typical imaging modalities used for preoperative staging are CT and MR imaging. Intraoperatively, CT or MR imaging cannot provide real-time guidance, and assessment by manual palpation is limited in precision. We investigated whether intraoperative sonography is a feasible technique for assessment of tumor thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…In another study by Yoon et al. ( 27 ) consisting of 22 patients, the mean sonographic DOI and histologic DOI were 6.6 ± 3.4 and 6.4 ± 4.4 mm, respectively, and there was excellent correlation between sonographic and histologic measurement for DOI, with a Pearson correlation coefficient of 0.95 (95%CI: 0.87–0.98). Filauro et al.…”
Section: Discussionmentioning
confidence: 85%
“…In another study by Yoon et al. ( 27 ) consisting of 22 patients, the mean sonographic DOI and histologic DOI were 6.6 ± 3.4 and 6.4 ± 4.4 mm, respectively, and there was excellent correlation between sonographic and histologic measurement for DOI, with a Pearson correlation coefficient of 0.95 (95%CI: 0.87–0.98). Filauro et al.…”
Section: Discussionmentioning
confidence: 85%
“…There are many comparative studies between r-DOI and p-DOI using ultrasound 8 , 19 or MRI 3 , 7 , 20 , 21 . Several studies stated that CT 22 , 23 is also useful for evaluation of r-DOI; however, CT cannot evaluate r-DOI when the contrast is low, superficial lesions cannot be detected, and metal artifacts often disturb images of tumor location.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological DOI (r-DOI) is frequently measured by CT, MRI, and ultrasound in tongue SCC. Previous studies have reported significant relationship between r-DOI measured on these modalities and pathological DOI (p-DOI) in the tongue SCC 8 12 . r-DOI differs from the tumor thickness (TT), and is defined as the distance from a virtual normal mucous membrane to the tumor’s deepest part on the image.…”
Section: Introductionmentioning
confidence: 97%
“…There are numerous studies suggested that preoperative or intraoperative US is reliable for the assessment of TT or DOI in oral cancer and can potentially guide the surgeon in the achievement of adequate resection margins, especially the deep margin ( Figure 1A and B ). 3 , 4 , 19 26 , 38 The correlation between the US-obtained and histology-obtained TT or DOI is good to strong with Spearman R = 0.760-0.988, 3 , 4 , 8 , 19 26 , 38 and some studies show that US is better than computed tomography (CT) and magnetic resonance imaging (MRI) at determining the deep margins of oral cancer. 8 , 22 , 26 , 39 , 40 This technique is reported to be particularly reliable in tongue cancers with TT or DOI under 10 mm.…”
Section: Pretreatment and Surgical Phasementioning
confidence: 99%